Discoid Medial Meniscus: A Case Report. Issue 2 (1st February 2016) - Dunn, John; Kusnezov, Nicholas; Waterman, Brian R.; Machen, Michael S.
ABSTRACT: Objectives: Here we present a rare finding of a discoid medial meniscus. Methods: Clinical reports, radiographs, magnetic resonance imaging (MRI) results, and intraoperative arthroscopic images highlight this rare clinical entity. Results: We have demonstrated successful treatment with arthroscopic partial meniscectomy and saucerization of discoid medial meniscus. Conclusions: Discoid medial menisci are a rare cause of medial knee pain and should be considered if classic MRI findings are associated with mechanical symptoms.